Effects of rasagiline on olfactory function in patients with Parkinson's disease. Issue 14 (4th November 2013) - Haehner, Antje; Hummel, Thomas; Wolz, Martin; Klingelhöfer, Lisa; Fauser, Mareike; Storch, Alexander; Reichmann, Heinz
ABSTRACT Background Impairment of olfactory function is a well‐recognized nonmotor manifestation of Parkinson's disease (PD). The aim of this investigation was to determine if the MAO‐B inhibitor rasagiline can improve olfaction in PD patients. Methods Thirty‐four PD patients participated in this single‐center, prospective, randomized, controlled, double‐blind study. Seventeen patients were randomly assigned to rasagiline and 17 patients to placebo. Ortho‐ and retronasal olfactory testing and recording of event‐related potentials were performed before and after 120 days of rasagiline versus placebo intake. Results When comparing olfactory score differences between baseline and after 120 days between the 2 groups, the level of significance was not reached. Conclusions The primary end point of the study was not reached, and therefore, a specific effect of rasagiline on olfactory function in PD could not be demonstrated. © 2013 International Parkinson and Movement Disorder Society